2022
DOI: 10.3389/fnmol.2022.824762
|View full text |Cite
|
Sign up to set email alerts
|

The Ameliorative Effect of JNK Inhibitor D-JNKI-1 on Neomycin-Induced Apoptosis in HEI-OC1 Cells

Abstract: Aminoglycosides can cause ototoxicity and lead to hair cell damage. Neomycin-induced ototoxicity is related to increased production of reactive oxygen species (ROS) and triggering hair cell apoptosis. The c-Jun-N-terminal kinase (JNK) pathway plays an essential role during hair cell damage. This study was designed to investigate an inhibitor of JNK, D-JNKI-1 (AM-111/brimapitide) in neomycin-induced HEI-OC1 cell apoptosis. The results demonstrate that neomycin increased intracellular ROS accumulation, which ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, we investigated the factors involved in VC opposed to neomycin-induced HEI-OC1 cell death. Previous studies have shown that JNK was activated by ROS which formed during oxidative stress [ 8 , 27 ], associated with neomycin-induced apoptosis via p38, MAPK, and JNK [ 6 ] activation in hair cells. JNK activation can be inhibited by antioxidants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we investigated the factors involved in VC opposed to neomycin-induced HEI-OC1 cell death. Previous studies have shown that JNK was activated by ROS which formed during oxidative stress [ 8 , 27 ], associated with neomycin-induced apoptosis via p38, MAPK, and JNK [ 6 ] activation in hair cells. JNK activation can be inhibited by antioxidants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS triggers various cell death mechanisms that include caspase-dependent or independent apoptosis and necrosis [ 4 , 5 ]. In addition to apoptosis induced by ROS, neomycin reportedly induces hair cell apoptosis via p38, MAPK, and JNK activation, as well [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous aminoglycoside-induced hair cell damage, neomycin significantly stimulated ROS production and activated program cell death in Tg transgenic zebrafish, considered a crucial target mechanism of otoprotective strategies. The ototoxic effects of neomycin have also been reported to involve c-Jun N-terminal kinase (JUN) and caspase-9 signal transduction [ 46 , 47 ]. Results from in vitro model of cochlear organotypic culture revealed that gentamicin dose-dependently induced outer and inner hair cells damage mediated by increasing ROS and reduced mitochondrial bioenergetics, which was attenuated via inhibition of apoptotic pathway [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…HEI-OC1 cells (kindly provided by Dr. Federico Kalinec, UCLA) were cultured under permissive conditions (33 °C, 10% CO 2 ) in high-glucose Dulbecco’s Eagle’s medium (DMEM) containing 10% fetal bovine serum (FBS) without antibiotics, as described in previous studies [ 31 , 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%